PERAN GURU BK DALAM MEMBERIKAN LAYANAN KONSELING INDIVIDU DENGAN TEKNIK SOLUTION-FOCUSED BRIEF COUNSELING (SFBC) UNTUK MENGATASI PERILAKU INDISIPLINER SISWA TERHADAP TATA TERTIB SEKOLAH DI SMK SAKTI GEMOLONG TAHUN PELAJARAN 2023/2024 - Tita Pramuditya Nastiti; Hera Heru Sri Suryanti; Ahmad Jawandi (CV. Adiba Aisha Amira, 2024)
The purpose of this study was to determine the role of guidance and counseling teachers in providing individual counseling services with solution-focused counseling techniques to overcome students' undisciplined behavior towards school rules at SMK Sakti Gemolong in the 2023/2024 Academic Year. This research was conducted at SMK Sakti Gemolong. The subject in this study was one of the students of class X TP-D. This research is a qualitative descriptive study, data collection for this study was carried out using observation, interviews, and documentation. The steps taken in analyzing are by compiling data, connecting data, reducing data, presenting data, then concluding. Meanwhile, to assess the validity of the data or the level of trustworthiness of the data presented, triangulation of sources from three different sources was used. The results of the study at SMK Sakti Gemolong showed that the implementation of individual counseling for students who behaved undisciplinedly (indiscipline) had been carried out well. The efforts of BK teachers play a role in providing individual counseling services with solution-focused counseling techniques to overcome students' undisciplined behavior by providing exception questions techniques, scaling questions techniques, and miracle questions techniques. The results obtained by students are able to improve their discipline, students are able to reduce undisciplined behavior that can harm themselves, students are able to control themselves, and students are able to carry out positive and useful activities. Undisciplined behavior can be overcome, students appear more diligent, orderly, and confident in their own abilities to become positive individuals.